Molecular plant-pathogen interactions with special reference to Eucalyptus Grandis polygalacturonase-inhibiting proteins and fungal polygalacturonases - Wingfield, Brenda D. (University of Pretoria, 2013)
Thesis (PhD (Plant Biotechnology))--University of Pretoria, 2006.